2013
DOI: 10.1002/anie.201300973
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of an Azahomoazafullerene C59N(NH)R and Gas‐Phase Formation of the Diazafullerene C58N2

Abstract: Open the cage if you dare: The azahomoazafullerene 1 was prepared from a tert‐butylperoxy‐substituted azafullerene derivative C59NBr(OOtBu)4. Singlet oxygen added to 1 to form an open‐cage azafullerene 2 with a ketoimide moiety on the rim of the orifice. The MALDI‐TOF mass spectrum of the product of the hydrolysis of 1 showed a clear signal for the diazafullerene C58N2 (see structure 3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…Fullerene-bound hydroxylamino group is prone to rearrangement as shown in our previous studies. [11,14,21] To expand the orifice we treated compound 4 with diacetoxyl iodobenzene (DIB). To our surprise, compound 5 with a CO molecule trapped in the cavity was isolated.…”
mentioning
confidence: 99%
“…Fullerene-bound hydroxylamino group is prone to rearrangement as shown in our previous studies. [11,14,21] To expand the orifice we treated compound 4 with diacetoxyl iodobenzene (DIB). To our surprise, compound 5 with a CO molecule trapped in the cavity was isolated.…”
mentioning
confidence: 99%
“…In conclusion, we have found that the acid-catalyzed arylation of variously N-substituted [5,6] open azafulleroids much depended on the nature of the substituents R (= alkyl, benzyl, and phenyl group), because the initial protonation of the incorporated bridged enamine framework varies with the substituents. Alkylazafulleroid brought about the monoarylation via the [5,6] ring closure and the protonated aminobridge opening.…”
Section: Azafulleroidmentioning
confidence: 97%
“…This reaction involves acid-induced C À N bond cleavage followed by the nucleophilic arylation and the closure of [5,6] open ring ( Table 1). The stronger protic acid CF 3 SO 3 H (TfOH) was practical for this arylation, similarly to the acidic arylation [a] Dr.…”
Section: Azafulleroidmentioning
confidence: 99%
See 2 more Smart Citations